PENGARUH GAYA HIDUP DAN PENDAPATAN TERHADAP KEPUTUSAN PEMBELIAN HELM KBC - Laksono, Dhimas Dwi; Iskandar, Donant Alananto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The study aims to determine whether there is influence between lifestyle and income on purchasing decision of KBC helmet. This study uses a quantitative approach through a survey to 109 users of KBC helmet. Sampling method is non probability sampling. The results of the hypothesis (t test) showed that lifestyle variables significantly influence purchasing decisions. This is indicated by t arithmetic of 13.198 which is greater than t table.However, the income variable has no significant effect on purchase decision with t -0.508 which is smaller than t table. The conclusion from this study that lifestyle variables are most dominant on purchasing decisions.This can be interpreted that, increasing purchasing decisions can be supported by the lifestyle of people who always want to look trend and always keep up with the times. Keywords: Lifestyle, income, purchase decision, helmet product.